Las redes sociales en comprensión de textos escritos en inglés en estudiantes de tercer grado de secundaria en instituciones educativas del distrito de San Juan Bautista 2021 - Rodríguez Sánchez, Lucero Anabel (2023)
The objective of this study was to explain the influence of social networks on third year students' English reading comprehension at San Juan Bautista district secondary schools 2021. The study was of explanatory type with field study, contemporary transectional, and multivariate designs. The population was composed of 840 students with stratified sample of 263 with proportional affixation. A written comprehension test and a Likert scale were used as data collection tools. Results show that the students have a low level of reading comprehension with a mean score of 5,67 out of 20 in pre-starter level. Similarly, in the indicators getting information 5,14, inference and interpretation 4, 69, all in pre-starter, except evaluation of text content, context, and format 7,17 at starter level. Regarding the use of social networks, they are at a somewhat adequate level 51,53 out of 100, and in the same way at a specific level: Facebook 51,54, YouTube 50,96, WhatsApp 54,39 and Facebook Messenger 48,55. It was concluded that social networks do not influence on reading comprehension as there is no correlation (r= 0,089; p-value= 0,148 > α =0,05), except for YouTube, but it does not influence in a better performance in reading comprehension either as B= 0,484 con p-valor = 0,477 > 0,05.